Comparative analysis of asbestos body and fiber content in formalin-fixed vs. paraffin-embedded lung tissue - Kuhn, Barbara K.; Vrugt, Bart; Low, Alex; Goodman, Julie E.; Attanoos, Richard (Frontiers in Public Health, 2025)
IntroductionAsbestos body and fiber burdens may be determined using different preparations of lung tissue. Paraffin-embedded tissue requires more complex steps than formalin-fixed tissue. A prior study highlighted potential variations in the measurement of retained mineral fibers in different lung preparations and prompted this expanded interlaboratory analysis. Data from exposed subjects referred to a Swiss laboratory were compared with the results of mineral analysis obtained from a laboratory based in the United Kingdom.MethodsNumbers of asbestos bodies were determined in formalin-fixed tissue and corresponding paraffin blocks of 62 subjects in Zurich by NaOCl digestion. Fiber burden was measured in a total of 104 subjects (62 subjects in Zurich and 42 subjects in Cardiff).ResultsAsbestos body and amphibole asbestos fiber counts obtained from paraffin blocks were noted to be, in general, lower than counts obtained from formalin-fixed tissue. The limits of detection were higher in paraffin blocks than in formalin-fixed tissue. Similar trends were obtained in the two laboratories.DiscussionIn this comparative mineral analytic study, the authors focused on the potential significance of differing specimen preparations (formalin-fixed wet lung versus paraffin wax-embedded block extraction) investigating paired samples. The results generally reflect numerically higher fiber burdens in samples analyzed from wet lungs compared with counterpart paraffin wax tissue. Mineral analysis by electron microscopic analysis remains the most objective measure of the respirable fraction of mineral dust as it correlates most directly with disease risk.